From 'bisexual' to 'queer': the radical sexuality of Paul Goodman. (1st October 2016) - Loftin, Craig M.
Abstract : This article explores the nature of Paul Goodman's sexuality within his historical context, arguing that his radical queerness influenced his social and political radicalism in important ways. His unrepentant homosexuality allowed him to identify as a social rebel, and it also broadened his understanding of the human condition. His visibility as a self-identified 'queer' provided a model for the early 1970s American gay liberation movement. Goodman's conservative attitudes about gender, however, also encouraged the sexism found in many 1960s American social movements.